The rise of mutual funds an insider's view - Fink, Matthew P. (New York : Oxford University Press, 2011)
In 1940 few Americans had heard of mutual funds. Today U.S. mutual funds are the largest financial industry in the world, with over 88 million shareholders and over $11 trillion in assets. New and updated to reflect the crash of 2008, 'The Rise of Mutual Funds' describes the developments that have produced mutual funds' long history of success.
"With full coverage of the 2008 crisis; second edition" -- Cover.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Mutual funds -- History